Pengembangan media busy book dalam meningkatkan kemampuan berhitung penjumlahan dan pengurangan kelas I SD Negeri Tamansari 3 Yogyakarta - Lestari, Marsha Ayu; Rhosyida, Nelly; Muanifah, Mahmudah Titi (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This study aims to develop and analyze the effectiveness of busy book learning media with the theme “Flora and Fauna of My Lucky Friends” on the counting ability of grade I students on the material of addition and subtraction of numbers 1 to 20 at SD Negeri Tamansari 3 Yogyakarta. This study uses a Research and Development (R&D) approach with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. The research sample involved 24 grade I students who used busy book media in learning. The research instruments included expert validation questionnaires, educator response questionnaires, and pre-test and post-test tests to measure counting skills. The results of the analysis showed that the busy book media met the eligibility criteria both valid, practical and effective. The validation score of media experts is 86% and material experts 83%, as well as practicality with an educator response score of 84%, all in the very feasible category. This media is proven effective in improving counting skills, with an increase in the average score from 48.75 in the pre-test to 92.5 in the post-test, and an N-Gain value of 0.86 (high category). The busy book media encourages students to learn actively through contextualized manipulative activities, increases motivation, and strengthens understanding of concrete mathematical concepts. This approach supports the goals of the Merdeka Curriculum in creating fun and meaningful learning for young children.